Resources
Testimonials
Plans
Sign in
Sign up
Resources
Testimonials
Plans
AI tutor
Welcome to Bytelearn!
Let’s check out your problem:
Solve the following equation for
x
x
x
. Express your answer in the simplest form.
\newline
x
+
7
−
4
=
1
2
(
2
x
−
4
)
+
6
x+7-4=\frac{1}{2}(2 x-4)+6
x
+
7
−
4
=
2
1
(
2
x
−
4
)
+
6
\newline
View step-by-step help
Home
Math Problems
Algebra 2
Evaluate variable expressions involving rational numbers
Full solution
Q.
Solve the following equation for
x
x
x
. Express your answer in the simplest form.
\newline
x
+
7
−
4
=
1
2
(
2
x
−
4
)
+
6
x+7-4=\frac{1}{2}(2 x-4)+6
x
+
7
−
4
=
2
1
(
2
x
−
4
)
+
6
\newline
Combine like terms:
Combine like terms on the left side of the equation.
\newline
x
+
7
−
4
x + 7 - 4
x
+
7
−
4
becomes
x
+
3
x + 3
x
+
3
.
\newline
So,
x
+
3
=
(
1
2
)
(
2
x
−
4
)
+
6
x + 3 = (\frac{1}{2})(2x - 4) + 6
x
+
3
=
(
2
1
)
(
2
x
−
4
)
+
6
.
Distribute the
(
1
/
2
)
(1/2)
(
1/2
)
:
Distribute the
(
1
/
2
)
(1/2)
(
1/2
)
on the right side of the equation.
(
1
/
2
)
(
2
x
)
−
(
1
/
2
)
(
4
)
(1/2)(2x) - (1/2)(4)
(
1/2
)
(
2
x
)
−
(
1/2
)
(
4
)
becomes
x
−
2
x - 2
x
−
2
. So,
x
+
3
=
x
−
2
+
6
x + 3 = x - 2 + 6
x
+
3
=
x
−
2
+
6
.
Combine like terms:
Combine like terms on the right side of the equation.
\newline
x
−
2
+
6
x - 2 + 6
x
−
2
+
6
becomes
x
+
4
x + 4
x
+
4
.
\newline
So,
x
+
3
=
x
+
4
x + 3 = x + 4
x
+
3
=
x
+
4
.
Subtract
x
x
x
:
Subtract
x
x
x
from both sides to get the
x
x
x
terms on one side.
\newline
x
+
3
−
x
=
x
+
4
−
x
x + 3 - x = x + 4 - x
x
+
3
−
x
=
x
+
4
−
x
.
\newline
This simplifies to
3
=
4
3 = 4
3
=
4
.
More problems from Evaluate variable expressions involving rational numbers
Question
Combine the like terms to create an equivalent expression:
\newline
2
s
+
(
−
4
s
)
=
0
2s+(-4s)=\boxed{\phantom{0}}
2
s
+
(
−
4
s
)
=
0
Get tutor help
Posted 1 year ago
Question
Combine the like terms to create an equivalent expression:
\newline
−
4
p
+
(
−
6
p
)
=
□
-4p+(-6p)=\square
−
4
p
+
(
−
6
p
)
=
□
Get tutor help
Posted 1 year ago
Question
Combine the like terms to create an equivalent expression:
\newline
4
z
−
(
−
3
z
)
=
□
4z-(-3z)=\square
4
z
−
(
−
3
z
)
=
□
Get tutor help
Posted 1 year ago
Question
Combine the like terms to create an equivalent expression:
\newline
r
+
(
−
5
r
)
=
0
r+(-5r)=\boxed{\phantom{0}}
r
+
(
−
5
r
)
=
0
Get tutor help
Posted 1 year ago
Question
Combine the like terms to create an equivalent expression:
\newline
−
4
p
+
(
−
2
)
+
2
p
+
3
=
-4p+(-2)+2p+3=
−
4
p
+
(
−
2
)
+
2
p
+
3
=
Get tutor help
Posted 1 year ago
Question
Rewrite the expression in the form
k
⋅
z
n
k \cdot z^{n}
k
⋅
z
n
.
\newline
Write the exponent as an integer, fraction, or an exact decimal (not a mixed number).
\newline
3
z
4
⋅
3
z
3
4
=
3 \sqrt[4]{z} \cdot 3 z^{\frac{3}{4}}=
3
4
z
⋅
3
z
4
3
=
Get tutor help
Posted 1 year ago
Question
Let
y
=
3
x
y=3^{x}
y
=
3
x
.
\newline
Find
d
2
y
d
x
2
\frac{d^{2} y}{d x^{2}}
d
x
2
d
2
y
\newline
d
2
y
d
x
2
=
\frac{d^{2} y}{d x^{2}}=
d
x
2
d
2
y
=
Get tutor help
Posted 1 year ago
Question
Let
y
=
4
x
2
+
3
x
2
x
−
7
y=\frac{4 x^{2}+3 x}{2 x-7}
y
=
2
x
−
7
4
x
2
+
3
x
.
\newline
d
y
d
x
=
\frac{d y}{d x}=
d
x
d
y
=
Get tutor help
Posted 1 year ago
Question
d
d
x
(
e
x
cos
(
x
)
)
=
\frac{d}{d x}\left(\frac{e^{x}}{\cos (x)}\right)=
d
x
d
(
c
o
s
(
x
)
e
x
)
=
Get tutor help
Posted 9 months ago
Question
Let
f
(
x
)
=
1
x
2
f(x)=\frac{1}{x^{2}}
f
(
x
)
=
x
2
1
.
\newline
f
′
(
5
)
=
f^{\prime}(5)=
f
′
(
5
)
=
Get tutor help
Posted 1 year ago
Related topics
Algebra - Order of Operations
Algebra - Distributive Property
`X` and `Y` Axes
Geometry - Scalene Triangle
Common Multiple
Geometry - Quadrant